2007
DOI: 10.1002/cncr.23199
|View full text |Cite
|
Sign up to set email alerts
|

Tumor mitotic rate, size, and location independently predict recurrence after resection of primary gastrointestinal stromal tumor (GIST)

Abstract: BACKGROUND. Gastrointestinal stromal tumor (GIST) is the most frequent sarcoma of the intestinal tract and often shows constitutive activation of either the KIT or PDGFRA receptor tyrosine kinases because of gain‐of‐function mutation. Although the efficacy of tyrosine kinase inhibitors in metastatic GIST depends on tumor mutation status, there have been conflicting reports on the prognostic importance of KIT mutation in primary GIST. METHODS. A total of 127 patients were studied who presented to our institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
328
8
18

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 436 publications
(375 citation statements)
references
References 41 publications
20
328
8
18
Order By: Relevance
“…Recently, some studies reported that GISTs with delWK557 -558 have an increased risk of relapse after curative surgery (Wardelmann et al, 2003;Martin et al, 2005;DeMatteo et al, 2008). In our study, GISTs with delWK557 -558 and GISTs with delTyr did not differ for the risk of relapse after curative surgery and both convey a poor prognosis.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Recently, some studies reported that GISTs with delWK557 -558 have an increased risk of relapse after curative surgery (Wardelmann et al, 2003;Martin et al, 2005;DeMatteo et al, 2008). In our study, GISTs with delWK557 -558 and GISTs with delTyr did not differ for the risk of relapse after curative surgery and both convey a poor prognosis.…”
Section: Discussionsupporting
confidence: 51%
“…KIT exon 11 deletions and deletions affecting codons 557 -558 of KIT exon 11 were described to be independent adverse prognostic factors in patients with GIST (Wardelmann et al, 2003;Martin et al, 2005;DeMatteo et al, 2008). Conversely, in another study, GISTs in which the last part of exon 11 (codons 562 -579) was deleted were most frequently associated with malignancy than GISTs with deletion of the first part of exon 11 (codons 550 -561; Emile et al, 2004Emile et al, , 2006.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…In this series, similar to our and others' previous reports, inferior disease-free survival was significantly associated with several clinicopathological factors, including older age (P ¼ 0.048), non-gastric location (P ¼ 0.035), presence of epithelioid histology (Po0.001), larger tumor size (Po0.001), higher mitotic count (Po0.001), and increasing NIH risk levels (Po0.001, Figure 4a). 5,6,9,13,[30][31][32][33] In addition, high proliferative index (Po0.001, Figure 4b) and unfavorable RTK genotypes (Po0.001, Figure 4c) were both highly predictive of adverse outcomes. It is noted that ezrin overexpression was also significantly associated with inferior disease-free survival (P ¼ 0.032, Figure 4d).…”
Section: Survival Analysesmentioning
confidence: 98%
“…15,21,23,25,26 Moreover, KIT exon 9 duplications, which occur mainly in intestinal tumors, have been associated with aggressive behavior. 21,25 A number of studies have also analyzed BRAF gene alterations in GISTs, reporting a mutation frequency of about 4e13%. 8e10 A predominant small intestinal location of GISTs with BRAF V600E has been observed, followed by a location in the stomach.…”
Section: Introductionmentioning
confidence: 99%